ON THE RELATIONSHIP OF THE UZBEK LANGUAGE WITH THE PERSIAN LANGUAGE (Scientific journal of the Fergana State University, 2024)
This article talks about Uzbek-Tajik relations, friendship and brotherhood, which has a long history, about the special place of borrowing words from the Persian-Tajik language into the Uzbek language, the spirituality and culture of the Uzbek and Tajik peoples, about the proximity to each other, about the influence of the Tajik language into Turkic languages during the reign of the Samanids, especially in the 13th-14th centuries, as a result of which official state documents began to be written in the Tajik language, poets and writers wrote in two languages, and changes occurred in the lexical richness of the two languages. After that, the Uzbek language began to acquire words from the Tajik language or, conversely, the Tajik language from the Uzbek language, so the connection of the language of the Uzbek people with the Iranian languages is characterized by three periodic features.